Improving cardiovascular risk stratification through the derivation and validation of an elevated triglyceride-glucose index - Mavraganis, Georgios; Georgiopoulos, Georgios; Athanasopoulos, Stavros; Terentes-Printzios, Dimitrios; Zervas, Georgios; Konstantaki, Christina; Koilakou, Maria Eleni; Giannakopoulou, Sofia-Panagiota; Dimopoulou, Maria-Angeliki; Chrysochoou, Christina; Tsioufis, Konstantinos; Pitsavos, Christos; et al. (Diabetes, obesity and metabolism, 2025)
Abstract Background and Aims Triglyceride-glucose (TyG) index, is an emerging prognostic biomarker in atherosclerotic cardiovascular disease (ASCVD). Validation of its clinical value and of clinically relevant prognostic cut-off, remains an unmet need to integrate TyG into primary prevention protocols. Methods To assess the clinical applicability of TyG, a composite of cardiovascular mortality, myocardial infarction, coronary revascularization or stroke was used as the primary endpoint in a general population cohort (ATTICA cohort, n?=?1677, derivation cohort). Next, we derived an optimal prognostic TyG cut-off and externally validated it in a primary prevention cohort (n?=?1237). To assess the clinical value of TyG, we analysed 1170 consecutively recruited patients from an ongoing registry aiming to stratify ASCVD risk (Athens Cardiometabolic Cohort) and assessed indices of subclinical arterial injury and progression of atherosclerosis. The TyG index was calculated by the formula: ln[fasting triglycerides (mg/dL)???fasting glucose (mg/dL)/2]. Results TyG index was independently associated with increased CVD events in the derivation cohort (HR?=?1.33, p?=?0.020). The incremental value of a derived optimal cut-off of 8.46 over SCORE2 was confirmed in both derivation and validation cohorts [net reclassification index (NRI)?=?0.668 and 0.469 respectively, Delta Harrell's C index?=?0.054 and 0.044 respectively, p?